1-methylhistamine as a potential biomarker of food histamine intolerance. A pilot study - Sánchez-Pérez, Sònia; Celorio-Sardà, Ricard; Veciana-Nogués, M. Teresa; Latorre-Moratalla, M. Luz; Comas-Basté, Oriol; Vidal-Carou, M. Carmen (Frontiers in Nutrition, 2022)
Efforts are currently being directed to identify a non-invasive marker that can serve as a solid and clinically irrefutable diagnostic criterion for histamine intolerance associated with diamine oxidase (DAO) deficiency. Accordingly, the identification of biomarkers of histamine (HA) metabolism in urine is proposed as a possible new diagnostic strategy. It is hypothesized that individuals with histamine intolerance could have a different urinary profile of HA and its metabolites in comparison with the healthy population. Thus, the aim of this study was to assess the urinary excretion of HA and 1-mehylhistamine (MHA) in individuals diagnosed with histamine intolerance and in a control group. Levels of HA and MHA were compared between 24-hour and first morning spot urine in a subgroup of 14 control individuals. Then, HA and MHA concentrations in spot urine of 32 histamine intolerant and 55 control individuals were determined by ultra-high performance liquid chromatography and fluorometric detection (UHPLC-FL) and normalized by creatinine. No differences were found between HA and MHA levels in 24-hour and first morning samples. Overall, histamine intolerant patients presented a distinct urinary excretion profile compared to the control group due to lower levels of MHA. No differences in urinary MHA were observed related to serum DAO activity. Spot urine samples were thus validated as a reliable tool to determine the urinary excretion of HA and MHA. These results constitute a starting point for the study of HA metabolomics as a suitable and non-invasive approach to histamine intolerance diagnosis.